Calcium Channels: Noteworthy Regulators and Therapeutic Targets in Dermatological Diseases - Wang, Min; Sun, Yaoxiang; Li, Linli; Wu, Peipei; DKW, Ocansey; Shi, Hui (Frontiers in Pharmacology, 2021)
Dysfunctional skin barrier and impaired skin homeostasis may lead to or aggravating a series of dermatologic diseases. In the process of skin wound healing and functional recovery, a large variety of biological events and bioactive molecules are involved. Calcium ion (Ca2+), particularly Ca2+ release from intracellular stores as well as Ca2+ influx through plasma membrane is essential to skin function. Growing evidences suggested calcium influx is mainly regulated by calcium-sensing receptors and channels, which can be classified into various types. Of these, voltage-gated, transient potential receptor, store-operated, and receptor-operated calcium channels not only regulate Ca2+ fluctuation, but also participate in cell proliferation and skin cell homeostasis through Ca2+-sensitive proteins such as calmodulin (CaM). Furthermore, distinct types of Ca2+ channels not merely work separately but may have interaction between each other. In this review, we discussed different calcium-sensing receptors and channels, particularly focusing on their regulatory functions as well as calcium channels-related reagents and drugs, which was expected to bridge basic research and clinical applications of dermatologic diseases.